Multiple Perspectives About the Supports Intensity Scale: What Is It Like to Sit at the Table? - Bartlett, Nadine; Khan, Eefa; Heringer, Rebeca; Kresta, Anne (Exceptionality Education International)

(untitled) (University of Western Ontario, 2026)
The Supports Intensity Scale – Adult Version (SIS-A) is a standardized assessment developed by the American Association of Intellectual and Developmental Disabilities that is designed to measure the support needs of persons with intellectual and developmental disabilities (IDD). The province of Manitoba, Canada, has adopted this assessment and administers it when persons with IDD reach the age of majority to measure individual support needs and to determine the allocation of public resources. As a part of a larger study examining the transition from school to adult life for young adults with disabilities in Manitoba, we investigated multiple participants’ satisfaction with, and perspectives about, the SIS-A. An online, anonymous survey was administered with persons with disabilities between the ages of 18 and 27, caregivers of persons with disabilities, educators, and service providers. A subset of participants (n = 143) indicated that they had participated in an SIS-A and were asked to rate their satisfaction with the SIS-A using a Likert scale and to “please explain” their response. Overall, satisfaction rates were low, with approximately one quarter of caregivers and one third of persons with disabilities and service providers reporting that they were satisfied or very satisfied. Educators reported the highest level of satisfaction at slightly over 50%. A thematic analysis of the open-ended survey responses (n = 98) regarding the participants’ satisfaction with the SIS-A revealed the following: (a) concerns about the accuracy of assessments, (b) inconsistent facilitation of the process, (c) potential for respondent-level factors to influence the outcome, (d) insufficient allocation of support using the seven-level supports budget framework and limited resources, (e) results not being used to enhance person-centred planning, and (f) the dehumanizing nature of the process. Based on these findings, a formal evaluation of the SIS-A in Manitoba is recommended, and suggestions for policy and practice are provided.